Peripheral blood CD4/CD19 cell ratio is an independent prognostic factor in classical Hodgkin lymphoma. Issue 7 (July 2014) - Gaudio, Francesco; Perrone, Tommasina; Mestice, Anna; Curci, Paola; Giordano, Annamaria; Delia, Mario; Pastore, Domenico; Specchia, Giorgina
Abstract Classical Hodgkin lymphoma (cHL) is characterized by the presence of tumoral cells in a rich background of T and B cells, macrophages and other inflammatory cells. The contribution of these non-tumoral cells to the pathogenesis of HL is still poorly understood. In our study we evaluated the prognostic significance of peripheral blood B, T and natural killer (NK) cells at diagnosis in 118 immunocompetent patients with cHL treated at our institution between January 2006 and December 2010. Fifty-four (46%) were male and 64 (54%) female. Median age at diagnosis was 33 years (range 15–82), and 71 patients (60%) presented an advanced stage (IIB–IV), 54 (46%) had bulky disease and 55 (47%) presented B symptoms. At the end of treatment, 94 patients (80%) had a complete response (CR) and 24 (20%) had a partial response. After a median follow-up of 54 months, 18 patients (15%) had relapsed. The variables that had a negative impact on progression-free survival (PFS) at univariate analysis were advanced stage, bone marrow involvement, International Prognostic Score (IPS) ≥ 3, positive interim positron emission tomography (int-PET), NK cells < 200/μL, CD19 cells < 85/μL, CD3/CD19 ratio ≥ 13 and CD4/CD19 ratio ≥ 10. At multivariate analysis, advanced stage, positive int-PET and CD4/CD19 ratio ≥ 10 were independent prognostic factors of PFS. New biological markers could be predictive of the response to treatment and survival in cHL. A CD4/CD19 ratio ≥ 10 seems to be associated with a worse outcome.